84.3k views
0 votes
Question is in the image Don't graph. I can do that

Question is in the image Don't graph. I can do that-example-1

1 Answer

6 votes

Given:


\begin{gathered} f(x)\text{ = }(1)/(2)(4)^x \\ g(x)\text{ = -}(1)/(2)(4)^x \end{gathered}

The value of the function at any point is obtained by substituting the point into the function.

f(0):


\begin{gathered} f(0)\text{ = }(1)/(2)(4)^0 \\ =\text{ }(1)/(2) \end{gathered}

f(1):


\begin{gathered} f(1)\text{ = }(1)/(2)(4)^1 \\ =\text{ 2} \end{gathered}

g(0):


\begin{gathered} g(0)\text{ = -}(1)/(2)(4)^0 \\ =-(1)/(2) \end{gathered}

g(1):


\begin{gathered} g(1)\text{ = -}(1)/(2)(4)^1 \\ =\text{ -2} \end{gathered}

User RSX
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.